Dailyboost / Siti Sarah Ahmad Jamil and Norfarhana Norazham - Ahmad Jamil, Siti Sarah; Norazham, Norfarhana (2022)
Daily boost is a company that manufactures products based on health supplements and skincare products named Forever Living that started operating in April 2022, based in Kuala Selangor. Our business plan is to aim strong market position on social media platforms and also to offer its products at a competitive price to meet the demand of our customers. Meanwhile, Daily boost is operating online by using a Facebook Page. The account was created in April 2022. Facebook pages really help to expand our business more. Dailyboost promotes the business to be more successful and known by using the soft sell and hard sell posting technique. Giving a teaser of the product and always posting to promote the business that will attract the customers to know more about our products and also buy. Malaysians are unwittingly participating in the new market trend of attempting due to the recent significant expansion seen by the supplement food-based business in Malaysia. Taking advantage of the chance, Dailyboost offers a wide selection of health supplements that will soon enable clients to conveniently grab their favourite goods. The company also plans to grow by opening more shops throughout Peninsular Malaysia. Dailyboost is a solid product option that may be further developed in a variety of markets as the company continues to flourish.